Parents' Perceptions Regarding Fulfilling Children's Nutritional Needs According to the Contents of My Plate in Pujon District - Afifah, Azzah; Hayyu Erfantini, Imro’atul (CV. Dyoqu Publishing Management, 2026)
Background:Providing adequate nutrition for early childhood is crucial for optimal growth and development. The government has strived to improve nutritional quality through the